Involvement of maternal grandmother and teenage mother in intervention to reduce pacifier use: a randomized clinical trial - Elsa Regina Justo Giugliani; Leandro Meirelles Nunes; Roberto Mário Silveira Issler; Lilian Cordova do Espírito Santo; Luciana Dias de Oliveira (Elsevier, 2019)
Objective: To assess the impact of an intervention for teenage mothers with the involvement of maternal grandmothers on the prevalence of pacifier use in the first six months of life. Methods: This randomized clinical trial involved 323 teenage mothers, allocated to four groups: intervention with teenagers only, intervention with teenagers and their mothers, and respective controls. Six breastfeeding counseling sessions, including the recommendation to avoid the use of a pacifier, were delivered at the maternity ward and subsequently at the teenagers' homes, at seven, 15, 30, 60, and 120 days postpartum. Data on infant feeding and pacifier use were collected monthly by interviewers blinded to group allocation. The impact of the intervention was measured by comparing survival curves for pacifier use in the first six months of life and mean time to pacifier introduction. Results: The intervention had a significant impact on reducing pacifier use only in the group in which grandmothers were involved. In this group, the intervention delayed by 64 days the introduction of a pacifier (21-85 days), compared to 25 days in the group without the participation of grandmothers (65-90 days). Conclusions: The intervention reduced pacifier use in the first six months of life and delayed its introduction until beyond the first month when grandmothers were involved. The intervention did not have a significant impact when only teenage mothers were involved. Resumo: Objetivo: Avaliar o impacto de uma intervenção para mães adolescentes com a participação de avós maternas na prevalência de uso de chupeta nos primeiros 6 meses de vida. Métodos: Este ensaio clínico randomizado envolveu 323 mães adolescentes, alocadas para quatro grupos: intervenção com somente adolescentes, intervenção com adolescentes e suas mães e respectivos controles. Seis sessões de aconselhamento para amamentação, incluindo a recomendação de evitar o uso de chupeta, foram realizadas na maternidade e posteriormente nas casas das adolescentes ao 7°, 15°, 30°, 60° e 120° dias. Os dados sobre alimentação infantil e uso de chupeta foram coletados mensalmente por entrevistadores cegos a respeito da alocação dos grupos. O impacto da intervenção foi medido comparando as curvas de sobrevida para uso de chupeta nos primeiros 6 meses de vida eotempo médio de introdução de chupetas. Resultados: A intervenção apresentou um impacto significativo sobre a redução do uso de chupeta somente no grupo em que as mães estiveram envolvidas. Nesse grupo, a intervenção mostrou atraso de 64 dias na introdução de chupeta (21 a 85 dias), em comparação a 25 dias no grupo sem a participação das avós (65 a 90 dias). Conclusões: A intervenção reduziu o uso de chupeta nos primeiros 6 meses de vida e atrasou sua introdução além do primeiro mês com a participação das avós. A intervenção não teve impacto significativo somente com o envolvimento das mães adolescentes. Keywords: Breastfeeding, Grandmother, Teenage mother, Pacifier, Clinical trial, Palavras-chave: Amamentação, Avó, Mãe adolescente, Chupeta, Ensaio clínico